The Alma Survey of Gas Evolution of Protoplanetary Disks (Age-Pro). Vii. Testing Accretion Mechanisms from Disk Population Synthesis - Miley, J; Gonzalez-Ruilova, C (Institute of Physics, 2025)
The architecture of planetary systems depends on the evolution of the disks in which they form. In this work, we develop a population synthesis approach to interpret the Atacama Large Millimeter/submillimeter Array survey of Gas Evolution of PROtoplanetary Disks (AGE-PRO) measurements of disk gas mass and size considering two scenarios: turbulence-driven evolution with photoevaporative winds and MHD wind-driven evolution. A systematic method is proposed to constrain the distribution of disk parameters from the disk fractions, accretion rates, disk gas masses, and CO gas sizes. We find that turbulence-driven accretion with initially compact disks (R0 ≃ 5-20 au), low mass-loss rates, and relatively long viscous timescales (tν,0 ≃ 0.4-3 Myr or αSS ≃ 2-4 × 10−4) can reproduce the disk fractions and gas sizes. However, the distribution of apparent disk lifetimes defined as the M D / M ̇ * ratio is severely overestimated by turbulence-driven models. On the other hand, MHD wind-driven accretion can reproduce the bulk properties of disk populations from Ophiuchus to Upper Scorpius assuming compact disks with an initial magnetization of about β ≃ 105 (αDW ≃ 0.5-1 × 10−3) and a magnetic field that declines with time. More studies are needed to confirm the low masses found by AGE-PRO, notably for compact disks that question turbulence-driven accretion. The constrained synthetic disk populations can now be used for realistic planet population models to interpret the properties of planetary systems on a statistical basis. © 2025. The Author(s). Published by the American Astronomical Society.